Detrital zircon signature of the Moine Supergroup, Scotland: Contrasts and comparisons with other Neoproterozoic successions within the circum-North Atlantic region - Kirkland, Chris; Strachan, R.; Prave, A. (Elsevier BV, 2008)
A total of 200 detrital zircon grains from three stratigraphically distinct samples of the Neoproterozoic Moine Supergroup, NW Scotland were analysed by ion microprobe. Samples were taken from the Lower and Upper Psammite Formations of the oldest Moine unit, the Morar Group, and one from the tectonostratigraphically overlying, and presumed younger, Glenfinnan Group. The Morar Group is dominated by Palaeo- and Mesoproterozoic crystals and minimal Archaean grains whereas the Glenfinnan Group has broadly the same overall age range but a greater proportion of Grenville (late Mesoproterozoic) detritus. These data indicate an increase up-section in Grenville-age detritus and a Laurentian provenance, consistent with initiation of Moine deposition during the final stages of development and exhumation of the Grenvillian Orogen. The youngest concordant detrital zircons provide maximum depositional ages for the Morar Group at 1022 ± 24 Ma and for the Glenfinnan Group at 1009 ± 22 Ma. Sedimentation must have ceased prior to 842 ± 20 Ma, the age of high temperature conditions recorded by magmatic zircon overgrowths in one of the Morar Group samples; this is compatible with mid-Neoproterozoic Knoydartian orogenic events documented elsewhere within the Moine Supergroup. Robust statistical comparison of the Moine detrital zircon age distributions to those from Neoproterozoic successions elsewhere enable definition of three main lithotectonic units: (1) late Mesoproterozic to early Neoproterozoic basins with a range of late Grenville intrusives; (2) mid- to late Neoproterozoic basins in extension-related intra-Rodinia settings or fringing Rodinia's oceanic margin; and (3) late Neoproterozoic to early Palaeozoic basins formed during the main phase of Rodinia break-up. Statistical comparisons also indicate that: (i) in Scotland, the Morar Group rocks are similar to the sub-Grampian Group rocks (Dava-Glen Banchor succession) and permit linkage with the Torridonian of the Caledonian foreland (Applecross and Ault Bea formations), but differ significantly from the Moinian Glenfinnan and Loch Eil groups, as well as the Dalradian rocks; and (ii) the provenance signal and depositional timing of the Moine compares closely to the Sørøy Succession of Arctic Norway and the lower Eleonore Bay Supergroup of East Greenland. All of these have a Laurentian affinity and thus tectonic models invoking a geologically exotic status (i.e., a terrane) for the Moine appear unnecessary. © 2008 Elsevier B.V. All rights reserved.